Strategi Komunikasi Dakwah Digital dalam Meningkatkan Literasi Hukum Ekonomi Syariah di Media Sosial - Intihaul Khiyaroh; Zaidatul Ishlahiyyah; Ahmad Masyhadi (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2026)
The development of social media has changed the pattern of da'wah communication, including the delivery of Sharia Economic Law literacy to the digital community, however the effectiveness of digital da'wah communication strategies in increasing this literacy still requires empirical study. This research aims to analyze how digital da'wah communication strategies are used to increase literacy in Sharia Economic Law and how the audience responds to da'wah content on social media. This research uses a qualitative approach with a content analysis method on 65 digital da'wah content on five Islamic preacher's Instagram accounts and sharia economic education platforms with ≥100,000 followers during the period January–December 2024. Data was collected through digital observation, content documentation, and audience interaction analysis, then analyzed thematically using a da'wah communication and sharia economic literacy framework. The research results show that effective communication strategies include the use of popular language based on muamalah fiqh, educational visualization through reels and infographics, as well as participatory interactivity that increases audience involvement. This strategy contributes to increasing literacy in cognitive, affective and conative aspects, as well as strengthening public trust in sharia economic preaching in the digital space.